Ecologia molecular, variabilidade genética, química e cultivo in vitro de Hesperozygis ringens Benth - Fracaro, Fernando (2006)
Hesperozygis ringens, belongs to Lamiaceae s family, it is an aromatic plant native from the South Brazil with its occurrence restrict south fields mainly in Caçapava do Sul, Alegrete and São Francisco de Assis. Due some activities agropastoris like continuous cleanness and burning to the renovation of grassland associate with some factors like low seed efficiency propagation, these spices are in extinction process. In order to evaluate the effect of these activities at the extinction process of this plant were used molecular markers RAPD and ISSR to evaluate the genetic variability, chemical variability of the essential oils and effect of the growing regulators in the micropropagation. With molecular markers we check a low gene flow between studied populations, with distinct genetic entities, sharing the samples in isolated clusters from Alegrete, São Francisco de Assis and Caçapava do Sul, the last one was evaluate in two populations A and B witch showed a larger gene flow between samples. The chemical variability data were confirmed by markers RAPD and ISSR, because they shared the populations in two isolated groups, characterized for to present compounds with low frequency like limonene and linalool in the São Francisco de Assis population, and the others were not present as sabinene in Caçapava do Sul. In the in vitro propagation the MS medium showed the best results supplemented with 13.2µM of benzyladenine and 2mg/l of silver nitrate, witch were used to avoid ethylene accumulation effect. The rooting showed limitation with low efficiency, but was obtained with carbonized rice back, with ¼ MS supplemented with IBA. Even with hardness the micropropagation can be an alternative for the propagation and preservations of this endangerous species. Based in this results of this work were discussed about environmental, evolution and conservation aspects.